Anatomical features and SCoT profiles provide new insight into phenotypic plasticity in the halophyte Suaeda maritima in Thailand - KANOKPHORN RITTIRONGSAKUL; ANITTHAN SRINUAL; Ongkarn Vanijajiva (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rittirongsakul K, Srinual A, Vanijajiva O. 2020. Anatomical features and SCoT profiles provide new insight into phenotypic plasticity in the halophyte Suaeda maritima in Thailand. Biodiversitas 21: 1082-1090. Phenotypic plasticity is the variation in phenotypic traits of organisms to survive with fluctuating environments. Halophytes are plants that can naturally tolerate high concentrations of salt in the soil, and their tolerance to salt stress, which reflects the ability of the plants to produce different phenotypic traits in response to changing environmental conditions. Suaeda maritima (L.) Dumort is a polymorphic halophyte and prominent species complex from tropical to temperate regions due to diverse stressful saline habitats. Consequently, the identification of S. maritima based on morphological data is challenging due to high phenotypic plasticity. In Thailand, S. maritima, known as Seablite or Cha Khram, has only been reported for the genus Suaeda which frequently found in coastal salt marshes. The peculiarities of the prevalence of three distinctive color traits, green, green-reddish and reddish, were commonly observed in Thailand. This preliminary study aims to examine the morpho-anatomical characters and molecular analysis of S. maritima and to determine how their morphological and genetic characterizations are related to phenotypic traits, particularly in color variation within the population at Bang Khun Tien shoreline in Bangkok, Thailand. This combined investigation of anatomical characters and start codon targeted (SCoT) fingerprinting profiles provide first evidence of phenotypic variations and genetic characterizations of halophytic S. maritima in Thailand. Anatomical characters of leaf structures confirmed that the species is austrobassioid (C3) types. Meanwhile, molecular investigation of thirty SCoT primers found that only two SCoT primers (SCoT10 and SCoT27) failed to amplify the S. maritima genomic DNA. Thoroughly, twenty-eight SCoT primers produced 162 unambiguous and reproducible banding profiles with 140-1200 bp product size. Despite, there was no genetic variation detectable within the population, SCoT technique was considered a suitable tool to produces adequate characterization for DNA fingerprinting of halophyte S. maritima. However, further studies involving additional samples of S. maritima are needed to obtain a more general view of the conspicuous variation and colonization history in Thailand.